A Macroeconomic Approach to Foreign Investment Flows in India - Chawla, Sonia; Sharma, Priyanka (Indian Journal of Finance, 2014)
The Indian economy, a developing economy and an attractive destination for foreign investment, has witnessed many ups and downs in its growth since its liberalization in 1991. Foreign investment in India has increased continuously since 1990-91 to 2010-11. Studies have shown that the major investment of FDI in India has been in the services sector. The movement of FDI and FIIs in India is affected by many macroeconomic variables like inflation, GDP, money supply, IIP, WPI, exchange rate, balance of trade, and so forth. The present paper conducts a review of studies in this area so as to establish a relation between macroeconomic variables and the inflow of foreign investment in India.